miR-106b is a novel target to promote muscle regeneration and restore satellite stem cell function in injured Duchenne dystrophic muscle - Lara Rodriguez-Outeiriño; Francisco Hernandez-Torres; Felicitas Ramirez de Acuña; Alberto Rastrojo; Carlota Creus; Alejandra Carvajal; Luis Salmeron; Marisol Montolio; Patricia Soblechero-Martin; Virginia Arechavala-Gomeza; Diego Franco; Amelia Eva Aranega (Elsevier, 2022)
Satellite cells (SCs), muscle stem cells, display functional heterogeneity, and dramatic changes linked to their regenerative capabilities are associated with muscle-wasting diseases. SC behavior is related to endogenous expression of the myogenic transcription factor MYF5 and the propensity to enter into the cell cycle. Here, we report a role for miR-106b reinforcing MYF5 inhibition and blocking cell proliferation in a subset of highly quiescent SC population. miR-106b down-regulation occurs during SC activation and is required for proper muscle repair. In addition, miR-106b is increased in dystrophic mice, and intramuscular injection of antimiR in injured mdx mice enhances muscle regeneration promoting transcriptional changes involved in skeletal muscle differentiation. miR-106b inhibition promotes the engraftment of human muscle stem cells. Furthermore, miR-106b is also high in human dystrophic muscle stem cells and its inhibition improves intrinsic proliferative defects and increases their myogenic potential. This study demonstrates that miR-106b is an important modulator of SC quiescence, and that miR-106b may be a new target to develop therapeutic strategies to promote muscle regeneration improving the regenerative capabilities of injured dystrophic muscle.